Magnetic properties of Fe intercalation FexTaSe2 - Feng, Qian-Qian; Guo, Jun-Jie; Zhong, Mian-Zeng; Luo, Zi-Yan; Li, Bo; Wang, Xi-Guang; Nie, Yao-Zhuang; Xia, Qing-Lin; Guo, Guang-Hua (Frontiers in Physics, 2024)
Intercalation of transition metal dichalcogenides with magnetic elements has been the subject of increasing research interest, aiming to explore novel magnetic materials with anisotropy and spin-orbit coupling. In this paper, two magnetic samples with varying Fe content have been prepared using different growth conditions via the chemical vapor transport method. A comprehensive investigation of the magnetic properties of the materials has been conducted using the Physical Property Measurement System (PPMS, EvercoolⅡ-9T, Quantum Design). The results reveal distinct features in the studied materials. Fe0.12TaSe2 exhibits significant ferromagnetism with a Curie transition temperature of 50 K. However, its in-plane magnetism is weak and no significant hysteresis loop is observed below the Curie temperature. On the other hand, Fe0.25TaSe2 exhibits antiferromagnetism without any hysteresis loop and has a Néel temperature up to 130 K. This finding is quite different from the intercalated iron in FexTaS2, where only an antiferromagnetic state occurs with x larger than 0.4. Our study thus provides updated insights into the magnetic properties of this new system and serves as a reference for future investigations of TaSe2 compounds with varying iron content.